Associations of chronic individual-level and neighbourhood-level stressors with incident coronary heart disease: the Multi-Ethnic Study of Atherosclerosis. Issue 2 (30th September 2014) - Kershaw, Kiarri N; Roux, Ana V Diez; Bertoni, Alain; Carnethon, Mercedes R; Everson-Rose, Susan A; Liu, Kiang
Abstract : Background: Several individual-level stressors have been linked to incident coronary heart disease (CHD), but less attention has focused on the influence of neighbourhood-level sources of stress. In this study we examined prospective associations of individual-level and neighbourhood-level stressors with incident CHD. Methods: Multi-Ethnic Study of Atherosclerosis participants aged 45–84 years at baseline (2000–2002) with complete data were included in the analyses (n=6678 for individual-level and n=6105 for neighbourhood-level stressors). CHD was defined as non-fatal myocardial infarction, resuscitated cardiac arrest or CHD death. Median follow-up was 10.2 years. Multivariable Cox proportional hazards models were fitted to estimate associations of individual-level and neighbourhood-level stressors (categorised into approximate tertiles) with incident CHD. Results: Higher reported individual-level stressors were associated with higher incident CHD. Participants in the high individual-level stressor category had 65% higher risk of incident CHD (95% CI 1.23 to 2.22) than those in the low category after adjusting for sociodemographics (P for trend=0.002). This association weakened but remained significant with further adjustment for behavioural and biological risk factors. There was a non-linear relationship between neighbourhood-level stressors and incident CHD (P for quadratic term=0.01). Participants in the medium category had 49% higher CHD risk (95% CI 1.06 to 2.10) compared with those in the low category; those in the high category had only 27% higher CHD risk (95% CI 0.83 to 1.95). These associations persisted with adjustment for risk factors and individual-level stressors. Conclusions: Individual-level and neighbourhood-level stressors were independently associated with incident CHD, though the nature of the relationships differed.